2014
DOI: 10.1080/17461391.2014.957729
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability to assess ventilatory threshold in ski‐mountaineering

Abstract: The capacity to predict the heart rate (HR) and speed at the first (VT1) and second (VT2) ventilatory thresholds was evaluated during an incremental ski-mountaineering test using heart rate variability (HRV). Nine skiers performed a field test to exhaustion on an alpine skiing track. VT1 and VT2 were individually determined by visual analysis from gas exchanges (VT1V and VT2V) and time-varying spectral HRV analysis (VT1fH, VT2fH and VT2H). VT1 could not be determined with the HRV methods used. On the contrary,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(57 citation statements)
references
References 45 publications
5
52
0
Order By: Relevance
“…For the spectral analysis, a short-term Fourier transform was applied with a moving window of 64 s and time shift of 10 s (Cassirame et al, 2015). The high-frequency band was extended (>0Á15-0Á4 Hz to >0Á15-2 Hz) to consider spectral energy content resulting from increases in respiratory frequency during high-intensity exercise (Cottin et al, 2006a,b).…”
Section: Gas Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…For the spectral analysis, a short-term Fourier transform was applied with a moving window of 64 s and time shift of 10 s (Cassirame et al, 2015). The high-frequency band was extended (>0Á15-0Á4 Hz to >0Á15-2 Hz) to consider spectral energy content resulting from increases in respiratory frequency during high-intensity exercise (Cottin et al, 2006a,b).…”
Section: Gas Analysismentioning
confidence: 99%
“…Based on the physiological mechanisms involving vagal withdrawal and the effects of hyperpnoea on high-frequency oscillations during high-intensity exercise, two techniques using HRV to indirectly detect both the VT and RCP have been investigated. The more complex of the two relies on the interaction between respiration frequency and autonomic innervation of the heart (Anosov et al, 2000;Cassirame et al, 2015;Cottin et al, 2006a,b;Mourot et al, 2014). However, recently it has been shown that both limb movement and respiration have the capacity to entrain within the power spectrum of the high-frequency band making its practicality questionable (Mendia-Iztueta et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although sport specific performance diagnosis and test protocols have been developed for nearly every type of sport (e. g. running, cycling, swimming, rowing, climbing,...) [14], no established method of performance diagnosis presently exists for skimo. While some studies have tried to use heart rate variability during field tests [1,9] to gain training recommendations and thresholds, others have focused on energy expenditure [2] or speed and optimal slope gradients [2,5,7]. All previous laboratory tests have used either roller skis [6], maximal running tests [2,4] or mountain running tests (stepwise increased slope) [4], with roller skis representing the closest approximation to skimo.…”
Section: Introductionmentioning
confidence: 99%
“…During submaximal exercise in apparently healthy subjects values as low as 6 ms have been reported . HRV analysis during exercise is also performed to determine ventilatory thresholds (Cassirame, et al, 2014;Mourot, et al, 2011). Initially, RRts were obtained from ECG recordings performed in laboratories or clinical environments and only ECG Holter monitoring was performed in an ambulatory setting.…”
Section: Discussionmentioning
confidence: 99%